Damocles' Sword But It Served To Remind Me Of What I Love Doing: A Supported Journey To Advance HE Fellowship At Dublin City University - Lisa Donaldson (Irish Journal of Academic Practice, 2022)
‘Sword of Damocles’ and a ‘marathon’, just some of the descriptions used by Advance HE Fellowship applicants on the first Supported journey to Fellowship at Dublin City University. In spite of such descriptions, this paper explores the successful journey to Fellowship for twenty one DCU applicants. It examines their motivations and the impacts of the journey, as well as comprehensively outlining the supportive building blocks designed to enable all applicants achieve Fellowship recognition. These building blocks include the creation of a knowledge base, Triad support and Work in Progress sessions. The study indicates that Fellows who were supported in this journey found it a positive experience despite the challenging nature of the process. Importantly, the respondents attest to the importance of community and collegiality as integral to the journey and the significance of the Fellowship supports to achieving Fellowship recognition. This study was completed to provide insight to the first institution wide Supported journey to Fellowship in Ireland. Findings will be useful to signpost supports to those in other institutions considering adopting Advance HE Fellowship as an approach to CPD for staff to engage with and improve their teaching.